Lenalidomide in combination with R-CHOP (R2-CHOP) as first-line treatment of patients with high tumour burden follicular lymphoma: a single-arm, open-label, phase 2 study. Issue 9 (September 2018) - Tilly, Hervé; Morschhauser, Franck; Casasnovas, Olivier; Molina, Thierry Jo; Feugier, Pierre; Gouill, Steven Le; Haioun, Corinne; Tournilhac, Olivier; Bouabdallah, Reda; Gabarre, Jean; Lamy, Thierry; Cabeçadas, José; et al.
Summary: Background: Immunochemotherapy with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) is a standard front-line treatment for follicular lymphoma. The combination of lenalidomide and rituximab has shown high efficacy in relapsed or refractory and untreated follicular lymphoma. We aimed to evaluate the safety and activity of the combination of lenalidomide and R-CHOP (R2-CHOP) in previously untreated patients with high burden follicular lymphoma. Methods: This single-arm, open-label, multicentre, phase 2 trial was done in 16 hospitals in France, all of which were Lymphoma Study Association (LYSA) sites. Eligible patients were aged 18–70 years and had previously untreated CD20-positive follicular lymphoma of grade 1, 2, or 3a; at least one high tumour burden criterion according to Groupe d'Etude des Lymphomes Folliculaires criteria; an Eastern Cooperative Oncology Group performance status score of 2 or less; and a minimum life expectancy of more than 3 months. Patients received induction therapy with six cycles of R2-CHOP every 3 weeks (one cycle involved standard R-CHOP on days 1–5, and 25 mg oral lenalidomide per day on days 1–14), followed by two rituximab infusions at 3-week intervals. The total treatment schedule was 24 weeks. Patients who achieved a complete or partial response to induction therapy received maintenance therapy consisting of one rituximab infusion every 8 weeks for 2 years. The primary outcome was the proportion of patients who achieved a complete response (complete response and complete response unconfirmed), according to International Workshop to Standardize Response Criteria, at the end of induction treatment. Safety was assessed in all patients who completed treatment. This trial is registered withClinicalTrials.gov, numberNCT01393756, and is closed to accrual. Findings: Between Dec 21, 2010, and Jan 25, 2012, 80 patients were enrolled, and 68 (85%) completed six cycles of R2-CHOP. At the end of the induction phase, 59 patients achieved a complete response (74%, 95% CI 63–83). 55 patients achieved a complete response at 30 months from enrolment (69%, 57–78). The most frequent adverse event was grade 4 neutropenia in 52 (65%) patients. The most frequent non-haematological side-effects included grade 1–2 sensory neuropathy in 28 (35%) patients and grade 1–2 transient rash in 27 (34%) patients. Four patients died during the study period; none of these deaths were judged to be related to treatment. Interpretations: Lenalidomide in combination with R-CHOP had an acceptable safety profile and showed anti-cancer activity in patients with previously untreated high burden follicular lymphoma. A future comparative study showing evidence of a survival advantage would be necessary for this combination to be proposed as a treatment for follicular lymphoma. Funding: French Ministry of Health, Celgene Corporation, and Amgen France.